2010
DOI: 10.1016/j.neuron.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

AMPA Receptor Signaling through BRAG2 and Arf6 Critical for Long-Term Synaptic Depression

Abstract: Central nervous system synapses undergo activity-dependent alterations to support learning and memory. Long-term depression (LTD) reflects a sustained reduction of the synaptic AMPA receptor content based on targeted clathrin-mediated endocytosis. Here we report a current-independent form of AMPA receptor signaling, fundamental for LTD. We found that AMPA receptors directly interact via the GluA2 subunit with the synaptic protein BRAG2, which functions as a guanine-nucleotide exchange factor (GEF) for the coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
208
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(223 citation statements)
references
References 66 publications
10
208
1
Order By: Relevance
“…Moreover, BRAG2 catalytic activity was stimulated by the cytoplasmic domain of GluA2 or a peptide derived from it. 8 Together these findings suggest that BRAG2 activity can be regulated by interactions with both lipids and proteins, perhaps simultaneously.…”
Section: Characteristics Of the Brag Subfamilymentioning
confidence: 90%
See 3 more Smart Citations
“…Moreover, BRAG2 catalytic activity was stimulated by the cytoplasmic domain of GluA2 or a peptide derived from it. 8 Together these findings suggest that BRAG2 activity can be regulated by interactions with both lipids and proteins, perhaps simultaneously.…”
Section: Characteristics Of the Brag Subfamilymentioning
confidence: 90%
“…7 In contrast, Kornau and colleagues demonstrated a direct interaction between BRAG2 and a non-phosphorylated tyrosine (Y876) in the cytoplasmic domain of the GluA2 subunit of neuronal AMPA receptors that required the PH domain. 8 In this case, phosphorylation of Y876 actually inhibited BRAG2 binding. Moreover, BRAG2 catalytic activity was stimulated by the cytoplasmic domain of GluA2 or a peptide derived from it.…”
Section: Characteristics Of the Brag Subfamilymentioning
confidence: 93%
See 2 more Smart Citations
“…Brag2 was found to promote the invasive activity of breast cancer cells [34] and myoblast fusion [11,37]. Furthermore, Brag2 was shown to be involved in trafficking processes such as the endocytosis of synaptic AMPA-receptors, E-Cadherin recycling, and phagocytosis of monocytes [21,46,47]. Silencing of Brag2 in HeLa cells increased the surface expression of b1-integrins [15] and a later study indicated that Brag2 might contribute to b1-integrin endocytosis in HeLa cells [33].…”
Section: Introductionmentioning
confidence: 97%